AB0374 Analysis of Spacing of The Intravenous Administration of Tocilizumab in Patients with Rheumatoid Arthritis. (15th July 2016) - Ito, S.; Kobayashi, D.; Takai, C.; Nemoto, T.; Lee, H.; Abe, A.; Otani, H.; Ishikawa, H.; Murasawa, A.; Narita, I.; Nakazono, K.
Abstract : Background: Although the biologic disease modified anti rheumatic drugs (bDMARDs) are the most effective treatment of rheumatoid arthritis (RA), the costs are much higher than those of conventional synthetic DMARDs (csDMARDs). A number of studies on discontinuation, dose reduction or spacing of bDMARDs have been performed, but there is almost no report of the spacing of tocilizumab (TCZ) so far. Objectives: To analyze the efficacy of spacing of the intravenous (iv) administration of TCZ in patients with RA. Methods: Enrolled were 63 patients (11 male, 52 female) who were administrated iv TCZ for more than 1 year. Eleven patients had shifted to subcutaneous injection and the data at the last iv infusion were analyzed. Results: Mean age was 57.4 years old (30–78), mean body weight was 55.5kg (37–85.5), mean duration of illness was 10.7years (0–32), Steinbrocker's Stage were 4/12/20/27, Class were 0/41/22/0, and the number of the former biologics were 0.9 (0–3), and duration of TCZ was 46.9 months (13–83). The intervals of administration were 4 weeks: 28.6%, 5 weeks: 38.1%, 6 weeks: 17.5%, 7 weeks: 6.0%, 8 weeks: 7.9%, 10 weeks: 1.6%. Tender joint count, swollen joint count, erythrocyte sedimentation rate (ESR), C-reactive protein, matrix metalloproteinase-3, patient's visual analogue scale (VAS), doctor's VAS, disease activity score (DAS) 28-ESR, simplified disease activity index (SDAI), and clinical DAI (CDAI) were significantly ameliorated. The remission rats were DAS28-ESR 90.5%, CDAI 44.4%, SDAI 42.9%, respectively. The number of patients with prednisolone (PSL) wer decreased from 50 patients at the initiating TCZ treatment to 38 patients (p=0.031), 4.2 (0–10) to 1.7 (0–5) mg/day (p<0.0001). Methotrexate (MTX) were used in 46 to 32 patients (p=0.017), 6.0 (0–18) to 3.3 (0–14) mg/weeks (p<0.0001). There were no changes in the usage of other csDMARDs. Conclusions: Spacing of the TCZ administration were done in 71.4% of the patients, even though it significantly reduced disease activity and reduced PSL and MTX. TCZ is the most inexpensive bDMARDs in Japan, but with spacing, it is possible to reduce more cost with a good control of RA. Further study of the analysis of the prevention of joint destruction by spacing is necessary. References: Smolen JS, Nash P, Durez P, et al. Maintenance, reduction, or withdrawal of etanercept after treatment with etanercept and methotrexate in patients with moderate rheumatoid arthritis (PRESERVE): a randomised controlled trial. Lancet 2013;381:918–29. Takeuchi T, Matsubara T, Ohta S, et al. Biologic-free remission of established rheumatoid arthritis after discontinuation of abatacept: a prospective, multicentre, observational study in Japan. Rheumatology (Oxford) 2015;54:683–91. Tanaka Y, Takeuchi T, Mimori T, et al. Discontinuation of infliximab after attaining low disease activity in patients with rheumatoid arthritis: RRR (remission induction by Remicade in RA) study. Ann Rheum Dis 2010;69:1286–91. Tanaka Y, Hirata S, Kubo S, et al. Discontinuation of adalimumab after achievingremission in patients with established rheumatoid arthritis: 1-year outcome of the HONOR study. Ann Rheum Dis 2015;74:389–95. Disclosure of Interest: None declared